Teaching Pragmatics to Indonesian Learners of English - Disa Evawani Lestari (English Education Study Program, Faculty of Education and Teachers Training, Tidar Univer, 2017)
Pragmatic competence constitutes a significant factor in determining the success of communication. In real life interaction, a language learner is not only expected to use language and produce utterances which are understandable or grammatically correct, but is also expected to produce utterances which are socioculturally appropriate. However, for students who learn English as a Foreign Language (EFL), the pragmatic competence, which can actually be acquired naturally through social interaction, is quite difficult to acquire due to the limited, if not absent at all, use of English to reach a communication goal in an authentic social interaction/setting (not in a role-play classroom activity). This paper aims to figure out some of those issues of teaching pragmatics in EFL classrooms in Indonesia and to explore the possible solutions based on the concept and approaches informed by the previous studies. The importance of the use of authentic materials, input and production activity, along with understandable feedback are highlighted as some of the ways to fill the lacking space in EFL learners’ pragmatic knowledge.erimental class and controlled class. The mean score of post-test (77.3) in experimental class was greater than the mean score of post-test (71.9) in controlled class and from t-test, the researcher found that the value of t-test (3.176) was greater than t-table (2.000) at the level of significances. It means that this is a significant difference between the result of the students’ pre-test and post-test. Therefore, H0 was rejected and H1was accepted. Based on the finding and discussion of the research, the researcher had drawn a conclusion that the use of Small Group Discussion Strategy in Improvingthe student’s reading comprehension at the Eleventh Grade Students of SMA Negeri 11 Bulukumba was effective.